MATLAB A Fundamental Tool for Scientific Computing and Engineering Applications - Volume 2 - Katsikis, Vasilios N. (IntechOpen, 2012)
This excellent book represents the second part of three-volumes regarding MATLAB- based applications in almost every branch of science. The present textbook contains a collection of 13 exceptional articles. In particular, the book consists of three sections, the first one is devoted to electronic engineering and computer science, the second is devoted to MATLAB/SIMULINK as a tool for engineering applications, the third one is about Telecommunication and communication systems and the last one discusses MATLAB toolboxes.